2018
DOI: 10.1101/444521
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbial and Metabolic Succession on Common Building Materials Under High Humidity Conditions

Abstract: 1Despite considerable efforts to characterize the ecology of bacteria and fungi in the built 2 environment (BE), the metabolic mechanisms underpinning their colonization and successional 3 dynamics remain unclear. Here, we applied bacterial/viral particle counting, qPCR, 16S and ITS 4 rRNA amplicon sequencing, and metabolomics to longitudinally characterize the ecological 5 dynamics of four commonly used building materials maintained at high humidity conditions 6 (~94% RH). We varied the natural inoculum provi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 15 publications
5
17
0
Order By: Relevance
“…The diversity of the microbiota is affected by multiple factors, including the host's genetic background, physiological condition, sex and age (Bing et al, 2013;Broderick et al, 2014). Environmental conditions, such as temperature, humidity and diet, also influence microbial composition (Wernegreen, 2012;Bing et al, 2018;Lax et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of the microbiota is affected by multiple factors, including the host's genetic background, physiological condition, sex and age (Bing et al, 2013;Broderick et al, 2014). Environmental conditions, such as temperature, humidity and diet, also influence microbial composition (Wernegreen, 2012;Bing et al, 2018;Lax et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Additional testing using pre-wetted swab heads, as performed in other built-environment studies [25][26][27][28][29], is warranted to determine if this would improve the ability of all swab types to detect SARS-CoV-2 in the hospital room environment. The detection of SARS-CoV-2 on ca.…”
Section: Discussionmentioning
confidence: 99%
“…362.5 copies per extraction for TMI) and (750–1450 copies per extraction for CGp and SYN) similar to that of other published studies (500 copies per extraction) [ 24 ]. Additional testing using pre-wetted swab heads, as performed in other built-environment studies [ 25 29 ], is warranted to determine if this would improve the ability of all swab types to detect SARS-CoV-2 in the hospital room environment. The detection of SARS-CoV-2 on ca .…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol extracts from surface swabs were evaporated to dryness and reconstituted in 200 µL of LCMS buffer. High resolution mass spectrometry analysis was performed according to previously reported procedures 23 . Analysis of LC-MS/MS data from the microbial swab extracts and the wood shavings was performed with Compound Discoverer 3.0 (Thermo Fisher), which identified metabolites as unique spectral features based on a combination of molecular weight and retention time.…”
Section: Microbial Metabolomics and Chemical Composition Analysis Unmentioning
confidence: 99%
“…Decades of research have shown that microbial (especially fungal) growth on building materials is enhanced under warm and humid conditions 17 22 . Furthermore, microbial growth is also enhanced under liquid wetting (i.e., soaked) conditions compared to when high humidity is the sole moisture source 23 . Microbial growth on material surfaces is also influenced by light, available nutrients, pH value, and even by the orientation of the material 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%